2016
DOI: 10.4172/2161-1165.1000264
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Libya, Cross-sectional Single Center Study

Abstract: Background: Chronic kidney disease (CKD) is a common problem globally and has heavy burden on patients and health authorities. Knowing the risk factors of CKD will reduce the prevalence of CKD and its socio-economic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(22 reference statements)
2
1
0
Order By: Relevance
“…Our result reveals that CGN is at the top of the known causes of ESRD in transplant recipients with 15%, this was in-line with a previous study by Habas et al, 16 who demonstrated that CGN is the first cause of CKD in the studied Libyan patients. In addition, Alashek et al 10 found that CGN in those less than 50 years of age was the most common cause (32.6%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our result reveals that CGN is at the top of the known causes of ESRD in transplant recipients with 15%, this was in-line with a previous study by Habas et al, 16 who demonstrated that CGN is the first cause of CKD in the studied Libyan patients. In addition, Alashek et al 10 found that CGN in those less than 50 years of age was the most common cause (32.6%).…”
Section: Discussionsupporting
confidence: 93%
“…17 However, this is unlike the case in many developed countries where the mean age of ESRD patients is generally over 60 years, 20 and the median age of the transplant recipients was 48 years. 21 Our result reveals that CGN is at the top of the known causes of ESRD in transplant recipients with 15%, this was inline with a previous study by Habas et al, 16 who demonstrated that CGN is the first cause of CKD in the studied Libyan patients. In addition, Alashek et al 10 found that CGN in those less than 50 years of age was the most common cause (32.6%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation